The history and future of correctional psychology - Magaletta, Philip R. (Springer, 2023)
"This edited volume provides a comprehensive overview of correctional psychology, considering the history and future of the practice. With contributions from expert leaders in the field of correctional psychology the application of psychological evaluation, treatment, and management of offenders in jails, prisons, and other correctional settings the early history is presented through a series of brief biographical sketches of the fields early pioneers. Moving forward, the period of growth and development of key concepts that advanced and